Isolation and Identification of Active Compounds from Ethanol Extract Piper crocatum Leaves as Antituberculosis Candidate - Rachmawaty, Farida Juliantina; Julianto, Tatang Shabur; Tamhid, Hady Anshory (Bangladesh Journal of Medical Science, 2025)
Background Treatment of tuberculosis is still a problem in Indonesia or in the world. There needs to be a new alternative drug for tuberculosis therapy. Objective The purpose of this study was to isolate and identify the active compounds from ethanol extract of red betel vine (Piper crocatum) leaves as an antituberculosis candidate. Methods The chloroform fraction of 70% ethanol extract was further purified, tested antimycobacterial activity against M. tuberculosis and identified its chemical structure using the method of Infra Red (FTIR) Spectrophotometer, UV-Vis Spectrophotometer and H/C-Nuclear Magnetic Resonance Spectrometer. Results Chloroform fraction identified 29 compounds.Compound 1 (S1) with Rf 0.96 has the best activity against M. tuberculosis with a minimum bactericidal concentration (MBC) of 5 μg/mL. The analysis of FTIR spectra and UV-Vis spectra, it is proposed that S1 compound is a triterpenoid compound which is hydroxylated and has more than one aliphatic alkene group. Conclusion The isolated compound with the best antimycobacterial activity against M. tuberculosis is suggested to be a hydroxylated triterpenoid containing multiple aliphatic alkene groups. BJMS, Vol. 24 No. 03 July’25 Page : 778-784